2016
DOI: 10.1002/2015jd023840
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological factors contributing to the interannual variability of midsummer surface ozone in Colorado, Utah, and other western U.S. states

Abstract: We use daily maximum 8 h average surface O3 concentrations (MDA8) for July 1995–2013, meteorological variables from the National Center for Environmental Prediction/National Center for Atmospheric Research Reanalysis, the North American Regional Reanalysis, and output from regional chemistry‐climate simulations to assess relationships between O3 and weather in the western U.S. We also explore relationships among July O3, satellite‐derived NO2, and meteorology. A primary objective of this study is to identify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 66 publications
(86 reference statements)
4
77
1
Order By: Relevance
“…Reddy and Pfister (2016) indicate that the Denver Cyclone is one of many potential terrain-related mechanism for limiting area-wide dispersion of O 3 and its precursors. Trace gas spatial distribution maps, provided in Figs.…”
Section: Photochemical Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reddy and Pfister (2016) indicate that the Denver Cyclone is one of many potential terrain-related mechanism for limiting area-wide dispersion of O 3 and its precursors. Trace gas spatial distribution maps, provided in Figs.…”
Section: Photochemical Processingmentioning
confidence: 99%
“…Many of these upslope flows can be caused by low-pressure formation in southern Colorado, a lee trough or line of lower pressure along the foothills, and the Denver Cyclone. The Denver Cyclone (Wilczak and Glendening, 1988;Wilczak and Christian, 1990;Szoke, 1991;Szoke et al, 2006) is a mesoscale cyclonic gyre which can form when there are southeasterly flows across the Palmer Divide (an east-to-west feature of higher terrain to the south of Denver) and a layer of high stability above the surface mixed layer and below 700 hPa (Szoke and Augustine, 1990;Reddy and Pfister, 2016). Reddy et al (1995) have shown that the Denver Cyclone plays a key role in the degradation of visibility and exceedances of the state visibility standard of 76 M m −1 during the winter, but our study is the first to examine the summertime impacts of the Denver Cyclone during an intensive air quality study with a detailed suite of aircraft and surface measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most studies on US ozone trends and variability tend to focus on ozone changes in a particular season and/or over a particular region -for example, summertime ozone Lu et al, 2016;Reddy and Pfister, 2016) over the eastern US (Zhang and Wang, 2016;Shen et al, 2015) or springtime ozone (Cooper et al, 2010) over the western US (M. Y. . Lin et al (2017) analyzed the various driving factors of the US MDA8 ozone trends by season and region, with no discussion on ozone at other hours.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of meteorology on tropospheric O 3 vary across the United States (US). Boundary layer height strongly and positively correlates with tropospheric O 3 in the western US (Reddy and Pfister, 2016). The O 3 -T relationship is positive in the eastern US but weakens and turns negative along a northsouth gradient, compared to the western US (Camalier et al, 2007;Tawfik and Steiner, 2013;Rasmussen et al, 2012;Reddy and Pfister, 2015).…”
Section: Introductionmentioning
confidence: 99%